Polyphenylene sulfide composite material and preparation method thereof

By adding functionalized glass fibers and reinforcement additives to the polyphenylene sulfide resin, the problem of dimensional shrinkage and insufficient interface bonding power at high temperatures is solved, and the toughness and wear resistance of the material are significantly improved.

CN120158095AActive Publication Date: 2025-06-17HUIZHOU ZHONGCHENG COMPOSITE MATERIAL TECH CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202510429659.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2025-06-17
Estimated Expiration
2045-04-08

AI Technical Summary

Technical Problem

Existing polyphenylene sulfide materials are prone to dimensional shrinkage or warping at high temperatures, which is difficult to meet the tolerance requirements of precision parts. At the same time, the bonding force between the fiber and the matrix is ​​insufficient, and layering is prone to occur for long-term use.

Method used

By adding functionalized glass fibers and reinforcement additives to the polyphenylene sulfide resin, the functionalized glass fibers are obtained by reacting amino grafted polyphenylene sulfide with silane-modified glass fibers. The reinforcement additives are vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene terpolymer and methyl methacrylate-butadiene-styrene terpolymer. Through interfacial chemical bonding and nano-reinforced phase and topological structure, the toughness and wear resistance of the material are improved.

Benefits of technology

It significantly improves the toughness and wear resistance of polyphenylene sulfide composite materials, while maintaining good mechanical strength and high temperature resistance, expanding the application range of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005347760840000151
    Figure BDA0005347760840000151
  • Figure BDA0005347760840000161
    Figure BDA0005347760840000161
Patent Text Reader

Abstract

The invention provides a polyphenylene sulfide composite material and a preparation method thereof, and belongs to the technical field of high polymer materials, the polyphenylene sulfide composite material comprises the following raw materials by weight: 130-150 parts of polyphenylene sulfide, 40-50 parts of functional glass fiber, 10-20 parts of a reinforcing aid, 3-6 parts of a compatilizer, 1-3 parts of a nucleating agent, 1-2 parts of a lubricant, and 1-2 parts of an antioxidant. Wherein the reinforcing auxiliary agent is a vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene terpolymer and / or a methyl methacrylate-butadiene-styrene terpolymer, and the reinforcing auxiliary agent is a vinyl fluoride-tetrafluoroethylene-hexafluoropropylene terpolymer and / or a methyl methacrylate-butadiene-styrene terpolymer; the functional glass fiber is obtained by reacting amino grafted polyphenylene sulfide with silane modified glass fiber. The polyphenylene sulfide composite material prepared by the invention not only has good mechanical properties and high temperature resistance, but also has excellent toughness and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polyphenylene sulfide composite material and a preparation method thereof. Background Art

[0002] Polyphenylene sulfide (PPS for short) is a semi-crystalline thermoplastic special engineering plastic. With its unique molecular structure and performance advantages, it has become an important raw material in the field of high-performance materials. The main chain of polyphenylene sulfide is composed of benzene rings and sulfur atoms connected alternately, which gives the material excellent high temperature resistance, chemical stability and flame retardancy, and the long-term use temperature can reach above 200°C. In addition, polyphenylene sulfide has high mechanical strength, good dimensional stability, and exhibits strong chemical corrosion resistance in acids, alkalis and organic solvents, making it widely used in high-end fields such as electronics, automobile manufacturing, and aerospace. For example, in the automotive field, polyphenylene sulfide is used to manufacture high-temperature resistant sensor housings; in the electronics field, its flame retardant properties are suitable for precision connectors; and in the environmental protection field, its corrosion resistance supports the long-term operation of chemical filtration equipment. With the global demand for lightweight and extreme environment resistant materials, the market size of polyphenylene sulfide continues to expand.

[0003] At present, the industrial production methods of polyphenylene sulfide include melt polycondensation and solution polycondensation. The melt polycondensation method directly reacts monomers at high temperature to generate polymers. Although the process is simple, it has the problems of harsh reaction conditions and difficult removal of by-products, resulting in a wide molecular weight distribution of the product and uneven mechanical properties. The solution polycondensation method uses polar solvents as the medium. Although it can improve molecular weight control, the solvent recovery cost is high and the residue is easy to contaminate the product, which limits the economic feasibility of large-scale production. In terms of composite material modification, traditional methods mostly use glass fiber or carbon fiber reinforcement. Although it can improve mechanical properties, the interface bonding between the fiber and the matrix is ​​insufficient, and long-term use is prone to stratification; while adding inorganic fillers can reduce costs, it significantly damages the toughness of the material. In addition, the existing process has limited ability to control the crystallinity of polyphenylene sulfide, resulting in the product being prone to dimensional shrinkage or warping at high temperatures, making it difficult to meet the tolerance requirements of precision parts. These problems have seriously restricted the further application of polyphenylene sulfide materials in high-end equipment manufacturing.

[0004] In recent years, many research reports have attempted to optimize the properties of polyphenylene sulfide materials through various means: for example, introducing nanofillers such as carbon nanotubes and graphene to enhance the thermal conductivity and strength of the composite materials, but the agglomeration problem of nanoparticles leads to uneven improvement in performance; using plasma treatment or silane coupling agents to improve the interfacial bonding between fibers and the matrix, but the process is complex and increases production costs; developing new catalyst systems such as ionic liquids to reduce the polycondensation temperature, but such catalysts have difficulties in recycling and possible environmental risks. Therefore, there is an urgent need to develop a new high-performance polyphenylene sulfide composite material and its preparation method, which not only has good high-temperature resistance and mechanical properties, but also has a significant improvement in toughness and impact resistance, thereby expanding the application range of polyphenylene sulfide composite materials. Summary of the Invention

[0005] The object of the present invention is to provide a preparation method of a polyphenylene sulfide composite material. By adding specific functionalized glass fibers and reinforcing aids to the polyphenylene sulfide resin, while maintaining good mechanical properties and high-temperature resistance of the material, the toughness and wear resistance of the material are further improved.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a polyphenylene sulfide composite material, which comprises the following raw material components by weight:

[0008] 130 - 150 parts of polyphenylene sulfide, 40 - 50 parts of functionalized glass fibers, 10 - 20 parts of reinforcing aids, 3 - 6 parts of compatibilizer, 1 - 3 parts of nucleating agent, 1 - 2 parts of lubricant, 1 - 2 parts of antioxidant.

[0009] Preferably, the preparation method of the functionalized glass fibers comprises the following steps:

[0010] Mix tetraisopropyl titanate with an ethanol aqueous solution, and dropwise add nitric acid under stirring, then stir to obtain a precursor solution; mix glass fibers with hydrochloric acid, heat and stir, filter, and dry to obtain pretreated glass fibers; mix the pretreated glass fibers with absolute ethanol, then add the precursor solution, heat and stir, let stand, filter, wash with water, and dry to obtain nano-TiO2 modified glass fibers; add the nano-TiO2 modified glass fibers and (3-glycidoxypropyl)methyldiethoxysilane into an ethanol aqueous solution, heat and stir, filter, and dry to obtain silane-modified glass fibers;

[0011] Concentrated nitric acid and concentrated sulfuric acid are mixed, then polyphenylene sulfide is added, heated to react, precipitated, filtered, and dried to obtain nitro-grafted polyphenylene sulfide; sodium borohydride, copper chloride and N-methylpyrrolidone are mixed, then nitro-grafted polyphenylene sulfide is added, heated to react, precipitated, filtered, and dried to obtain amino-grafted polyphenylene sulfide; amino-grafted polyphenylene sulfide is mixed with N-methylpyrrolidone, then silane-modified glass fiber is added, heated to react, reduced pressure distillation is performed, and dried to obtain functionalized glass fiber.

[0012] In the raw material formula of the polyphenylene sulfide composite material, the present invention adopts functionalized modified glass fiber, thereby significantly improving the toughness and wear resistance of the material, and at the same time ensuring that the composite material has good mechanical strength and high temperature resistance.

[0013] During the preparation process, the surface of the glass fiber is first etched with hydrochloric acid to form a micro-nanoscale rough structure, and then nano-TiO2 particles are loaded through the sol-gel method. The high hardness of the nano-TiO2 particles forms a physical interlock with the polyphenylene sulfide matrix, enhancing the load transfer efficiency. At the same time, the epoxy group of 3-glycidoxypropylmethyldiethoxysilane undergoes a ring-opening reaction with the amino group of the subsequent amino-grafted polyphenylene sulfide, constructing a covalent bond bridging network between the fiber and the matrix, which significantly improves the interfacial bonding force, effectively inhibits crack propagation and promotes energy dissipation. The loaded nano-TiO2 not only acts as a rigid reinforcement phase to resist the plowing effect during wear, but its surface hydroxyl groups can also form hydrogen bonds with the silane structure to synergistically strengthen the interface, while the amino-grafted polyphenylene sulfide molecular chain and the matrix polyphenylene sulfide form a continuous phase through chain entanglement and co-crystallization effect, further blurring the interface phase region. During the dynamic friction process, the chemically bonded interface reduces the generation of abrasive particles caused by fiber-matrix debonding, and the high thermal conductivity of nano-TiO2 accelerates the diffusion of friction heat to avoid adhesive wear caused by local temperature rise. In addition, the multi-scale rough structure on the surface of the functionalized glass fiber increases the real contact area, makes the stress distribution more uniform, and delays the occurrence of fatigue wear. The present invention uses the synergistic effect of the above-mentioned interface chemical bonding, nano-reinforced phase and topological structure to enable the composite material to absorb energy through multiple mechanisms such as fiber pullout, crack deflection and interface plastic deformation when subjected to impact, and inhibits material loss through the hard protective layer and stable interface during wear, thereby achieving a simultaneous improvement in toughness and wear resistance.

[0014] Preferably, the weight ratio of tetraisopropyl titanate, ethanol aqueous solution and nitric acid is 7-15:40-60:5-10; the weight ratio of the pretreated glass fiber and the precursor solution is 7-15:20-40; the weight ratio of the nano-TiO2 modified glass fiber and (3-glycidoxypropyl)methyldiethoxysilane is 10-20:0.5-1.

[0015] Preferably, the weight ratio of concentrated nitric acid, concentrated sulfuric acid, and polyphenylene sulfide is 40 - 50:1 - 10:2 - 8; the weight ratio of sodium borohydride, copper chloride, and nitro-grafted polyphenylene sulfide is 1 - 3:0.3 - 0.8:2 - 5; the weight ratio of amino-grafted polyphenylene sulfide and silane-modified glass fiber is 1 - 3:4 - 6.

[0016] Furthermore, the preparation method of the functionalized glass fiber includes the following steps:

[0017] Mix 7 - 15 parts by weight of tetra-isopropyl titanate with 40 - 60 parts by weight of an 80 - 90 wt% ethanol aqueous solution, and dropwise add 5 - 10 parts by weight of 10 - 15 wt% nitric acid under stirring conditions of 22 - 27°C and 200 - 400 rpm. The dropping time is 10 - 20 min. After the dropping is completed, continue stirring for 20 - 30 min to obtain a precursor solution; mix 7 - 15 parts by weight of glass fiber with 40 - 60 parts by weight of 1 - 2 wt% hydrochloric acid, stir at 60 - 70°C and 200 - 400 rpm for 3 - 5 h, filter, and dry to obtain pretreated glass fiber; mix 7 - 15 parts by weight of pretreated glass fiber with 50 - 70 parts by weight of absolute ethanol, then add 20 - 40 parts by weight of the precursor solution, stir at 50 - 60°C and 200 - 400 rpm for 30 - 50 min, then let it stand for 3 - 5 h, filter, wash with water until neutral, and dry to obtain nano-TiO₂ modified glass fiber; add 10 - 20 parts by weight of nano-TiO₂ modified glass fiber and 0.5 - 1 part by weight of (3-glycidoxypropyl)methyldiethoxysilane to 50 - 70 parts by weight of a 40 - 50 wt% ethanol aqueous solution, stir at 70 - 75°C and 80 - 150 rpm for 40 - 60 min, filter, and dry to obtain silane-modified glass fiber;

[0018] Mix 40 - 50 parts by weight of 55 - 65 wt% concentrated nitric acid and 1 - 10 parts by weight of 92 - 98 wt% concentrated sulfuric acid, then add 2 - 8 parts by weight of polyphenylene sulfide, and react at 50 - 60 °C and 50 - 100 rpm for 1 - 2 h. After the reaction, add it to 100 - 200 parts by weight of 70 - 85 wt% methanol aqueous solution for precipitation, filtration, and drying to obtain nitro - grafted polyphenylene sulfide; mix 1 - 3 parts by weight of sodium borohydride, 0.3 - 0.8 parts by weight of copper chloride with 40 - 60 parts by weight of N - methylpyrrolidone, then add 2 - 5 parts by weight of nitro - grafted polyphenylene sulfide, and react at 55 - 65 °C and 50 - 100 rpm for 0.5 - 2 h. After the reaction, add it to 100 - 200 parts by weight of 70 - 85 wt% methanol aqueous solution for precipitation, filtration, and drying to obtain amino - grafted polyphenylene sulfide; mix 1 - 3 parts by weight of amino - grafted polyphenylene sulfide with 70 - 150 parts by weight of N - methylpyrrolidone, then add 4 - 6 parts by weight of silane - modified glass fiber, and react at 60 - 70 °C and 50 - 100 rpm for 10 - 15 h. After the reaction, recover N - methylpyrrolidone by vacuum distillation and dry to obtain functionalized glass fiber.

[0019] Preferably, the reinforcing aid is vinylidene fluoride - tetrafluoroethylene - hexafluoropropylene terpolymer and / or methyl methacrylate - butadiene - styrene terpolymer.

[0020] The present invention also adds a specific combination of reinforcing aids to the polyphenylene sulfide composite material formulation, and through their synergistic effect, further improves the wear resistance and high - temperature resistance of the material.

[0021] Among them, the fluorinated segments of the vinylidene fluoride - tetrafluoroethylene - hexafluoropropylene terpolymer form a rigid network at high temperatures, and its low surface energy reduces the friction coefficient and inhibits thermal oxidative degradation. The core - shell structure of the methyl methacrylate - butadiene - styrene terpolymer (the butadiene rubber phase is dispersed in the styrene - methyl methacrylate rigid matrix) improves toughness through the energy - dissipation mechanism of crazing shear bands. The polar matching between the vinylidene fluoride - tetrafluoroethylene - hexafluoropropylene terpolymer and polyphenylene sulfide promotes the uniform dispersion of fluorocarbon segments in the matrix, forms physical cross - link points to limit the high - temperature slip of molecular chains, and improves the high - temperature resistance. At the same time, the benzene ring structure of the methyl methacrylate - butadiene - styrene terpolymer and the benzene sulfide unit produce a π - π stacking effect, enhancing the interfacial bonding force; during the wear process, the fluorinated surface of the vinylidene fluoride - tetrafluoroethylene - hexafluoropropylene terpolymer preferentially migrates to the friction interface to form a self - lubricating transfer film, while the elastic phase of the methyl methacrylate - butadiene - styrene terpolymer reduces the initiation of microcracks through deformation buffering. The two work together to reduce the wear rate. This dual - phase reinforcement system breaks through the performance bottleneck of single - component materials in high - temperature wear - resistant scenarios through the complementarity of rigidity - flexibility and interfacial chemistry synergy.

[0022] Further, the enhancing agent is a mixture composed of vinylidene fluoride - tetrafluoroethylene - hexafluoropropylene terpolymer and methyl methacrylate - butadiene - styrene terpolymer in a weight ratio of 2 - 4:1.

[0023] Preferably, the compatibilizer is at least one of ethylene - acrylate - maleic anhydride copolymer, maleic anhydride grafted ethylene - octene copolymer, and polyolefin grafted glycidyl methacrylate.

[0024] Further, the compatibilizer is ethylene - acrylate - maleic anhydride copolymer.

[0025] Preferably, the nucleating agent is at least one of talc, calcium carbonate, magnesium carbonate, silica, and mica powder.

[0026] Further, the nucleating agent is talc.

[0027] Preferably, the lubricant is at least one of pentaerythritol stearate, ethylene bisstearamide, glycerol monostearate, polyvinyl alcohol, and liquid paraffin.

[0028] Further, the lubricant is a mixture composed of pentaerythritol stearate and ethylene bisstearamide in a weight ratio of 1 - 3:3.

[0029] Preferably, the antioxidant is at least one of antioxidant 1010, antioxidant 616, and antioxidant 1076.

[0030] Further, the antioxidant is antioxidant 1010.

[0031] The present invention also provides a preparation method of the above - mentioned polyphenylene sulfide composite material, which includes the following steps:

[0032] Weigh polyphenylene sulfide, functionalized glass fiber, enhancing agent, compatibilizer, nucleating agent, lubricant, and antioxidant according to the raw material formula, then add them into a high - speed mixer for mixing, and then add them into a twin - screw extruder for melt - blending and extrusion granulation to obtain the polyphenylene sulfide composite material.

[0033] Preferably, the rotation speed of the high - speed mixer is 400 - 600 rpm, and the mixing time is 7 - 15 min.

[0034] Preferably, the twin - screw extrusion process is as follows: the extrusion temperature is 270 - 340 °C, and the screw rotation speed is 200 - 500 rpm.

[0035] Furthermore, the twin-screw extrusion process is: zone one temperature 275-285°C, zone two temperature 285-295°C, zone three temperature 285-295°C, zone four temperature 325-335°C, zone five temperature 325-335°C, zone six temperature 295-305°C, and the screw speed is 300-400rpm.

[0036] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0037] 1. The present invention provides a method for preparing a polyphenylene sulfide composite material, by adding specific functionalized glass fibers and reinforcing agents into polyphenylene sulfide resin, wherein the functionalized glass fibers are obtained by reacting amino-grafted polyphenylene sulfide with silane-modified glass fibers, and the reinforcing agent is a vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene terpolymer and / or a methyl methacrylate-butadiene-styrene terpolymer, so that the material not only has good mechanical properties and high temperature resistance, but also further improves the toughness and wear resistance of the material, thereby expanding the application range of the polyphenylene sulfide composite material.

[0038] 2. The present invention adds self-made functionalized glass fiber, and the surface of the glass fiber is etched with hydrochloric acid to form a micro-nano rough structure, and nano-TiO2 particles are loaded. These high-hardness particles are physically interlocked with the matrix to enhance the load transfer efficiency; 3-glycidoxypropylmethyldiethoxysilane and amino-grafted polyphenylene sulfide construct a covalent bond bridging network between the fiber and the matrix, which significantly improves the interfacial bonding force, inhibits crack propagation and promotes energy dissipation; amino-grafted polyphenylene sulfide and the matrix form a continuous phase through chain entanglement and co-crystallization effect, blurs the interface phase region, and the chemically bonded interface in dynamic friction reduces the generation of abrasive particles caused by fiber-matrix debonding. Nano-TiO2 accelerates friction heat diffusion to avoid local temperature rise causing adhesive wear, so that the composite material absorbs energy when it is subjected to impact, and the hard protective layer and stable interface inhibit material loss during wear, thereby achieving a simultaneous improvement in toughness and wear resistance.

[0039] 3. The present invention uses vinylidene fluoride - tetrafluoroethylene - hexafluoropropylene terpolymer and / or methyl methacrylate - butadiene - styrene terpolymer as reinforcing additives. Due to the presence of fluorine atoms in its molecular chain, the vinylidene fluoride - tetrafluoroethylene - hexafluoropropylene terpolymer has extremely high chemical stability and thermal stability, which can effectively improve the high-temperature resistance of the composite material. Moreover, its surface energy is low and the friction coefficient is small, which helps to enhance the wear resistance of the material. The methyl methacrylate - butadiene - styrene terpolymer has good elasticity and can form fine dispersed phases inside the material to absorb and disperse external stress, preventing crack propagation, thereby further increasing the wear resistance of the material. Through the synergistic effect of the two polymers, a more uniform and stable microstructure can be constructed inside the material, optimizing the stress distribution, increasing the melting temperature, and enabling the composite material to have more excellent wear resistance and high-temperature resistance while maintaining high strength. Detailed Embodiments

[0040] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0041] Polyphenylene sulfide, grade: NHU 1170C, manufacturer: Zhejiang NHU Special Materials Co., Ltd.

[0042] Glass fiber, monofilament diameter: 11μm, length: 4.5mm, manufacturer: Tai'an Yilin New Materials Co., Ltd.

[0043] Vinylidene fluoride - tetrafluoroethylene - hexafluoropropylene terpolymer, grade: VitonAL - 600, manufacturer: DuPont Company, USA.

[0044] Methyl methacrylate - butadiene - styrene terpolymer, grade: EXL - 2690, manufacturer: Rohm and Haas Company, USA.

[0045] Ethylene - acrylate - maleic anhydride copolymer, grade: Grafting rate 1.3%, manufacturer: Arkema Company, France.

[0046] Talc powder, fineness: 2000 mesh, manufacturer: Qingdao Lukuang Talc Powder Co., Ltd.

[0047] Example 1

[0048] This example provides a polyphenylene sulfide composite material, which comprises the following raw materials by weight:

[0049] 140 parts by weight of polyphenylene sulfide, 45 parts by weight of functionalized glass fiber, 15 parts by weight of reinforcing aid, 5 parts by weight of compatibilizer, 2 parts by weight of nucleating agent, 1.5 parts by weight of lubricant, 1.5 parts by weight of antioxidant.

[0050] Among them, the reinforcing aid is a mixture composed of a vinylidene fluoride - tetrafluoroethylene - hexafluoropropylene terpolymer and a methyl methacrylate - butadiene - styrene terpolymer in a weight ratio of 3:1. The compatibilizer is an ethylene - acrylate - maleic anhydride copolymer. The nucleating agent is talcum powder. The lubricant is a mixture composed of pentaerythritol stearate and ethylene bisstearamide in a weight ratio of 2:3. The antioxidant is antioxidant 1010.

[0051] The preparation method of the functionalized glass fiber includes the following steps:

[0052] Mix 10 parts by weight of tetra - isopropyl titanate with 50 parts by weight of 85 wt% ethanol aqueous solution, and drop - add 8 parts by weight of 12 wt% nitric acid under the stirring conditions of 25 °C and 300 rpm. The dropping time is 15 min. After the dropping is completed, continue to stir for 25 min to obtain a precursor solution; mix 10 parts by weight of glass fiber with 50 parts by weight of 1.8 wt% hydrochloric acid, stir at 65 °C and 300 rpm for 4 h, filter, and dry to obtain pretreated glass fiber; mix 10 parts by weight of pretreated glass fiber with 60 parts by weight of absolute ethanol, then add 30 parts by weight of the precursor solution, stir at 55 °C and 300 rpm for 40 min, then stand for 4 h, filter, wash with water until neutral, and dry to obtain nano - TiO₂ modified glass fiber; add 15 parts by weight of nano - TiO₂ modified glass fiber and 0.75 parts by weight of (3 - glycidoxypropyl) methyldiethoxysilane to 60 parts by weight of 45 wt% ethanol aqueous solution, stir at 72 °C and 100 rpm for 50 min, filter, and dry to obtain silane - modified glass fiber;

[0053] Mix 45 parts by weight of 60 wt% concentrated nitric acid and 5 parts by weight of 95 wt% concentrated sulfuric acid, then add 5 parts by weight of polyphenylene sulfide, react at 55 °C and 80 rpm for 1.5 h. After the reaction, add it to 150 parts by weight of 80 wt% methanol aqueous solution for precipitation, filtration, and drying to obtain nitro-grafted polyphenylene sulfide; mix 2 parts by weight of sodium borohydride, 0.5 parts by weight of copper chloride with 50 parts by weight of N-methylpyrrolidone, then add 3 parts by weight of nitro-grafted polyphenylene sulfide, react at 60 °C and 80 rpm for 1 h. After the reaction, add it to 150 parts by weight of 80 wt% methanol aqueous solution for precipitation, filtration, and drying to obtain amino-grafted polyphenylene sulfide; mix 2 parts by weight of amino-grafted polyphenylene sulfide with 100 parts by weight of N-methylpyrrolidone, then add 5 parts by weight of silane-modified glass fiber, react at 65 °C and 80 rpm for 12 h. After the reaction, recover N-methylpyrrolidone by vacuum distillation and dry to obtain functionalized glass fiber.

[0054] This example provides a method for preparing a polyphenylene sulfide composite material, which includes the following steps:

[0055] Weigh polyphenylene sulfide, functionalized glass fiber, reinforcing aid, compatibilizer, nucleating agent, lubricant, and antioxidant according to the raw material formula, then add them to a high-speed mixer and mix at 500 rpm for 10 min, and then add them to a twin-screw extruder for melt blending and extrusion granulation to obtain the polyphenylene sulfide composite material. Among them, the twin-screw extrusion process is: the temperature of the first zone is 280 °C, the temperature of the second zone is 290 °C, the temperature of the third zone is 290 °C, the temperature of the fourth zone is 330 °C, the temperature of the fifth zone is 330 °C, the temperature of the sixth zone is 300 °C, and the screw speed is 350 rpm.

[0056] Example 2

[0057] This example provides a polyphenylene sulfide composite material, which includes the following raw material components by weight:

[0058] 130 parts by weight of polyphenylene sulfide, 40 parts by weight of functionalized glass fiber, 10 parts by weight of reinforcing aid, 3 parts by weight of compatibilizer, 1 part by weight of nucleating agent, 1 part by weight of lubricant, 1 part by weight of antioxidant.

[0059] Among them, the reinforcing aid is a mixture composed of vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene terpolymer and methyl methacrylate-butadiene-styrene terpolymer in a weight ratio of 2:1. The compatibilizer is ethylene-acrylate-maleic anhydride copolymer. The nucleating agent is talc powder. The lubricant is a mixture composed of pentaerythritol stearate and ethylene bis-stearamide in a weight ratio of 1:3. The antioxidant is antioxidant 1010.

[0060] The preparation method of the functionalized glass fiber is the same as that in Example 1.

[0061] This embodiment provides a method for preparing a polyphenylene sulfide composite material, which includes the following steps:

[0062] Weigh polyphenylene sulfide, functionalized glass fiber, reinforcing aid, compatibilizer, nucleating agent, lubricant and antioxidant according to the raw material formula, then add them into a high-speed mixer and mix at 400 rpm for 7 minutes, and then add them into a twin-screw extruder for melt blending and pelletizing to obtain the polyphenylene sulfide composite material. Among them, the twin-screw extrusion process is as follows: the temperature of the first zone is 275 °C, the temperature of the second zone is 285 °C, the temperature of the third zone is 285 °C, the temperature of the fourth zone is 325 °C, the temperature of the fifth zone is 325 °C, the temperature of the sixth zone is 295 °C, and the screw speed is 300 rpm.

[0063] Example 3

[0064] This embodiment provides a polyphenylene sulfide composite material, which includes the following raw material components by weight:

[0065] 150 parts by weight of polyphenylene sulfide, 50 parts by weight of functionalized glass fiber, 20 parts by weight of reinforcing aid, 6 parts by weight of compatibilizer, 3 parts by weight of nucleating agent, 2 parts by weight of lubricant, 2 parts by weight of antioxidant.

[0066] Among them, the reinforcing aid is a mixture composed of vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene terpolymer and methyl methacrylate-butadiene-styrene terpolymer in a weight ratio of 4:1. The compatibilizer is ethylene-acrylate-maleic anhydride copolymer. The nucleating agent is talc powder. The lubricant is a mixture composed of pentaerythritol stearate and ethylene bisstearamide in a weight ratio of 3:3. The antioxidant is antioxidant 1010.

[0067] The preparation method of the functionalized glass fiber is the same as that in Example 1.

[0068] This embodiment provides a method for preparing a polyphenylene sulfide composite material, which includes the following steps:

[0069] Weigh polyphenylene sulfide, functionalized glass fiber, reinforcing aid, compatibilizer, nucleating agent, lubricant and antioxidant according to the raw material formula, then add them into a high-speed mixer and mix at 600 rpm for 15 minutes, and then add them into a twin-screw extruder for melt blending and pelletizing to obtain the polyphenylene sulfide composite material. Among them, the twin-screw extrusion process is as follows: the temperature of the first zone is 285 °C, the temperature of the second zone is 295 °C, the temperature of the third zone is 295 °C, the temperature of the fourth zone is 335 °C, the temperature of the fifth zone is 335 °C, the temperature of the sixth zone is 305 °C, and the screw speed is 400 rpm.

[0070] Comparative Example 1

[0071] The difference between this comparative example and Example 1 is that the preparation method of the functionalized glass fiber is different, specifically as follows: The preparation method of the functionalized glass fiber includes the following steps:

[0072] Mix 10 parts by weight of glass fiber with 50 parts by weight of 1.8 wt% hydrochloric acid, stir at 65 °C and 300 rpm for 4 h, filter, wash with water until neutral, and dry to obtain pretreated glass fiber; Add 15 parts by weight of pretreated glass fiber and 0.75 parts by weight of (3-glycidoxypropyl)methyldiethoxysilane to 60 parts by weight of 45 wt% aqueous ethanol solution, stir at 72 °C and 100 rpm for 50 min, filter, and dry to obtain silane-modified glass fiber;

[0073] Mix 45 parts by weight of 60 wt% concentrated nitric acid and 5 parts by weight of 95 wt% concentrated sulfuric acid, then add 5 parts by weight of polyphenylene sulfide, react at 55 °C and 80 rpm for 1.5 h, after the reaction is completed, add it to 150 parts by weight of 80 wt% methanol aqueous solution for precipitation, filter, and dry to obtain nitro-grafted polyphenylene sulfide; Mix 2 parts by weight of sodium borohydride, 0.5 parts by weight of copper chloride with 50 parts by weight of N-methylpyrrolidone, then add 3 parts by weight of nitro-grafted polyphenylene sulfide, react at 60 °C and 80 rpm for 1 h, after the reaction is completed, add it to 150 parts by weight of 80 wt% methanol aqueous solution for precipitation, filter, and dry to obtain amino-grafted polyphenylene sulfide; Mix 2 parts by weight of amino-grafted polyphenylene sulfide with 100 parts by weight of N-methylpyrrolidone, then add 5 parts by weight of silane-modified glass fiber, react at 65 °C and 80 rpm for 12 h, after the reaction is completed, recover N-methylpyrrolidone by vacuum distillation, and dry to obtain functionalized glass fiber.

[0074] Comparative Example 2

[0075] The difference between this comparative example and Example 1 is that the preparation method of the functionalized glass fiber is different, specifically as follows: The preparation method of the functionalized glass fiber includes the following steps:

[0076] Mix 10 parts by weight of tetra-isopropyl titanate with 50 parts by weight of 85 wt% aqueous ethanol solution, dropwise add 8 parts by weight of 12 wt% nitric acid under stirring conditions at 25 °C and 300 rpm, the dropping time is 15 min, after the dropping is completed, continue to stir for 25 min to obtain a precursor solution; Mix 10 parts by weight of glass fiber with 50 parts by weight of 1.8 wt% hydrochloric acid, stir at 65 °C and 300 rpm for 4 h, filter, and dry to obtain pretreated glass fiber; Mix 10 parts by weight of pretreated glass fiber with 60 parts by weight of absolute ethanol, then add 30 parts by weight of the precursor solution, stir at 55 °C and 300 rpm for 40 min, then stand for 4 h, filter, wash with water until neutral, and dry to obtain nano-TiO2 modified glass fiber;

[0077] Mix 45 parts by weight of 60 wt% concentrated nitric acid and 5 parts by weight of 95 wt% concentrated sulfuric acid, then add 5 parts by weight of polyphenylene sulfide, react at 55 °C and 80 rpm for 1.5 h. After the reaction is completed, add it to 150 parts by weight of 80 wt% methanol aqueous solution for precipitation, filtration, and drying to obtain nitro-grafted polyphenylene sulfide; mix 2 parts by weight of sodium borohydride, 0.5 parts by weight of copper chloride with 50 parts by weight of N-methylpyrrolidone, then add 3 parts by weight of nitro-grafted polyphenylene sulfide, react at 60 °C and 80 rpm for 1 h. After the reaction is completed, add it to 150 parts by weight of 80 wt% methanol aqueous solution for precipitation, filtration, and drying to obtain amino-grafted polyphenylene sulfide; mix 2 parts by weight of amino-grafted polyphenylene sulfide with 100 parts by weight of N-methylpyrrolidone, then add 5 parts by weight of nano-TiO₂ modified glass fiber, react at 65 °C and 80 rpm for 12 h. After the reaction is completed, recover N-methylpyrrolidone by vacuum distillation, and dry to obtain functionalized glass fiber.

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 1 is that the preparation method of the functionalized glass fiber is different, specifically as follows: The preparation method of the functionalized glass fiber includes the following steps:

[0080] Mix 10 parts by weight of tetra-isopropyl titanate with 50 parts by weight of 85 wt% ethanol aqueous solution, and dropwise add 8 parts by weight of 12 wt% nitric acid under stirring conditions at 25 °C and 300 rpm. The dropping time is 15 min. After the dropping is completed, continue stirring for 25 min to obtain a precursor solution; mix 10 parts by weight of glass fiber with 50 parts by weight of 1.8 wt% hydrochloric acid, stir at 65 °C and 300 rpm for 4 h, filter, and dry to obtain pretreated glass fiber; mix 10 parts by weight of pretreated glass fiber with 60 parts by weight of absolute ethanol, then add 30 parts by weight of the precursor solution, stir at 55 °C and 300 rpm for 40 min, then stand for 4 h, filter, wash with water until neutral, and dry to obtain nano-TiO₂ modified glass fiber; add 15 parts by weight of nano-TiO₂ modified glass fiber and 0.75 parts by weight of (3-glycidoxypropyl)methyldiethoxysilane to 60 parts by weight of 45 wt% ethanol aqueous solution, stir at 72 °C and 100 rpm for 50 min, filter, and dry to obtain silane-modified glass fiber;

[0081] Mix 2 parts by weight of polyphenylene sulfide with 100 parts by weight of N-methylpyrrolidone, then add 5 parts by weight of silane-modified glass fiber, react at 65 °C and 80 rpm for 12 h. After the reaction is completed, recover N-methylpyrrolidone by vacuum distillation, and dry to obtain functionalized glass fiber.

[0082] Comparative Example 4

[0083] The difference between this comparative example and Example 1 is as follows: The preparation method of the functionalized glass fiber is different, specifically as follows: The preparation method of the functionalized glass fiber includes the following steps:

[0084] Mix 10 parts by weight of glass fiber with 50 parts by weight of 1.8 wt% hydrochloric acid, stir at 65 °C and 300 rpm for 4 h, filter, wash with water until neutral, and dry to obtain pretreated glass fiber;

[0085] Mix 2 parts by weight of polyphenylene sulfide with 100 parts by weight of N-methylpyrrolidone, then add 5 parts by weight of pretreated glass fiber, react at 65 °C and 80 rpm for 12 h, after the reaction, recover N-methylpyrrolidone by vacuum distillation, and dry to obtain functionalized glass fiber.

[0086] Comparative Example 5

[0087] The difference between this comparative example and Example 1 is as follows: The reinforcing aid is different, and the reinforcing aid is a terpolymer of vinylidene fluoride - tetrafluoroethylene - hexafluoropropylene.

[0088] Comparative Example 6

[0089] The difference between this comparative example and Example 1 is as follows: The reinforcing aid is different, and the reinforcing aid is a terpolymer of methyl methacrylate - butadiene - styrene.

[0090] Performance Test

[0091] The polyphenylene sulfide composites prepared in Examples 1 - 3 and Comparative Examples 1 - 6 were injection molded by an injection molding machine to obtain samples, and the following performance tests were carried out. Among them, the tensile strength was determined by the method in GB / T 1040.2 - 2022 "Plastics - Determination of tensile properties - Part 2: Test conditions for moulding and extrusion plastics", 1B type dumbbell specimens, 10 groups in parallel for each example, and the average value was taken. The notched impact strength was determined by the method in GB / T 1843 - 2008 "Plastics - Determination of cantilever beam impact strength", the specimen was of A type notch, 10 groups in parallel for each example, and the average value was taken. The abrasion resistance was determined by the method in GB / T 3960 - 2016 "Plastics - Methods of sliding friction and wear test", the load was 300 N, the friction rate was 2 m / s, the friction time was 120 min, 10 groups in parallel for each example, and the average value was taken. The melting temperature was determined by the method in GB / T 19466.3 - 2004 "Plastics - Differential scanning calorimetry (DSC) - Part 3: Determination of melting and crystallization temperatures and enthalpies", 10 groups in parallel for each example, and the average value was taken. The results are shown in Table 1.

[0092] Table 1: Results of various performance tests of polyphenylene sulfide composites

[0093]

[0094]

[0095] From the above performance test results, it can be seen that the polyphenylene sulfide composites prepared in Examples 1-3 have excellent tensile strength, notched impact strength, abrasion resistance and high temperature resistance. In particular, the polyphenylene sulfide composite prepared in Example 1 has the best comprehensive performance. This is because in the present invention, by using specific functionalized glass fibers and reinforcing aids, while ensuring that the polyphenylene sulfide composite has good mechanical properties (tensile strength) and high temperature resistance (melting temperature), the toughness (notched impact strength) and abrasion resistance of the composite are further improved. By comparing Example 1 with Comparative Examples 1-4, it can be seen that since the functionalized glass fibers prepared by a specific method were not used in Comparative Examples 1-4, the test results such as the notched impact strength, abrasion resistance and tensile strength of the polyphenylene sulfide composite are significantly worse than those of Example 1; by comparing Example 1 with Comparative Examples 5-6, it can be seen that since the reinforcing aids composed of vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene terpolymer and methyl methacrylate-butadiene-styrene terpolymer were not used in Comparative Examples 5-6, the test results such as their abrasion resistance and high temperature resistance are worse than those of Example 1. In summary, through the comparison of the above test results, the importance of the technical solution defined in the present invention for its technical effects is further proved.

[0096] The above is the preferred embodiment of the present invention. It should be pointed out that for those of ordinary skill in the art, without departing from the principle described in the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. A polyphenylene sulfide composite material, characterized in that: By weight, it includes the following raw materials: 130-150 parts of polyphenylene sulfide, 40-50 parts of functionalized glass fiber, 10-20 parts of reinforcing agent, 3-6 parts of compatibilizer, 1-3 parts of nucleating agent, 1-2 parts of lubricant, 1-2 parts of antioxidant; the reinforcing agent is vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene terpolymer and / or methyl methacrylate-butadiene-styrene terpolymer.

2. The polyphenylene sulfide composite material according to claim 1, characterized in that: The method for preparing the functionalized glass fiber comprises the following steps: The tetraisopropyl titanate is mixed with an ethanol aqueous solution, nitric acid is added dropwise under stirring, and the mixture is stirred to obtain a precursor solution; the glass fiber is mixed with hydrochloric acid, heated and stirred, filtered, and dried to obtain a pretreated glass fiber; The pretreated glass fiber is mixed with anhydrous ethanol, and a precursor solution is added, heated and stirred, allowed to stand, filtered, and dried to obtain nano-TiO2 modified glass fiber; the nano-TiO2 modified glass fiber and (3-glycidoxypropyl)methyldiethoxysilane are added to an ethanol aqueous solution, heated and stirred, filtered, and dried to obtain silane modified glass fiber; Concentrated nitric acid and concentrated sulfuric acid are mixed, polyphenylene sulfide is added, heated to react, precipitated, filtered, and dried to obtain nitro-grafted polyphenylene sulfide; sodium borohydride, copper chloride and N-methylpyrrolidone are mixed, nitro-grafted polyphenylene sulfide is added, heated to react, precipitated, filtered, and dried to obtain amino-grafted polyphenylene sulfide; amino-grafted polyphenylene sulfide is mixed with N-methylpyrrolidone, silane-modified glass fiber is added, heated to react, reduced pressure distillation is performed, and drying is performed to obtain functionalized glass fiber.

3. The polyphenylene sulfide composite material according to claim 2, characterized in that: The weight ratio of tetraisopropyl titanate, ethanol aqueous solution and nitric acid is 7-15:40-60:5-10; the weight ratio of the pretreated glass fiber and the precursor solution is 7-15:20-40; the weight ratio of the nano-TiO2 modified glass fiber and (3-glycidoxypropyl)methyldiethoxysilane is 10-20:0.5-1.

4. The polyphenylene sulfide composite material according to claim 2, characterized in that: The weight ratio of concentrated nitric acid, concentrated sulfuric acid and polyphenylene sulfide is 40-50:1-10:2-8; the weight ratio of sodium borohydride, cupric chloride and nitro-grafted polyphenylene sulfide is 1-3:0.3-0.8:2-5; the weight ratio of amino-grafted polyphenylene sulfide and silane-modified glass fiber is 1-3:4-6.

5. The polyphenylene sulfide composite material according to claim 1, characterized in that: The reinforcing auxiliary agent is a mixture of a vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene terpolymer and a methyl methacrylate-butadiene-styrene terpolymer in a weight ratio of 2-4:

1.

6. The polyphenylene sulfide composite material according to claim 1, characterized in that: The compatibilizer is at least one of ethylene-acrylate-maleic anhydride copolymer, maleic anhydride grafted ethylene-octene copolymer, and polyolefin grafted glycidyl methacrylate; the nucleating agent is at least one of talc, calcium carbonate, magnesium carbonate, white carbon black, and mica powder.

7. The polyphenylene sulfide composite material according to claim 1, characterized in that: The lubricant is at least one of pentaerythritol stearate, ethylene bisstearamide, glyceryl stearate, polyvinyl alcohol, and liquid paraffin.

8. The polyphenylene sulfide composite material according to claim 7, characterized in that: The lubricant is a mixture of pentaerythritol stearate and ethylene bisstearamide in a weight ratio of 1-3:

3.

9. The polyphenylene sulfide composite material according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1010 , antioxidant 616 , and antioxidant 1076 .

10. The method for preparing a polyphenylene sulfide composite material according to any one of claims 1 to 9, characterized in that: The steps include: Polyphenylene sulfide, functionalized glass fiber, reinforcing agent, compatibilizer, nucleating agent, lubricant and antioxidant are weighed according to the raw material formula, then added into a high-speed mixer for mixing, then added into a twin-screw extruder for melt blending, extruded and granulated to obtain the polyphenylene sulfide composite material.

Citation Information

Patent Citations

  • Laminated body, molded article, electroconductive pattern, electronic circuit, and electromagnetic shield

    CN107708997A

  • Chemical copper plating solution

    CN108165959A

  • Polyphenylene sulfide material and preparing method thereof

    CN110066513A

  • High-wear-resistance polyphenylene sulfide material and preparation method thereof

    CN110615988A

  • High-toughness wear-resistant polyphenylene sulfide composite material

    CN110643179A